2021
DOI: 10.21240/mpaed/40/2021.11.19.x
|View full text |Cite
|
Sign up to set email alerts
|

CoViD-19 als Katalysator für die digitale Professionalisierung angehender Lehrpersonen?

Abstract: Die CoViD-19-Pandemie ab Frühjahr 2020 und die pandemiebedingten Kontaktbeschränkungen hatten erhebliche Auswirkungen auf die studienbegleitenden Praxisphasen im Lehramtsstudium. Studierende, die ihr Praxissemester im Sommersemester 2020 absolvierten, waren in der Folge erheblich von Einschränkungen sowohl während der universitären Begleitveranstaltungen als auch in den Praxisschulen betroffen. Durch die überwiegende Umstellung von Präsenzformaten zu digitalem Lehren und Lernen auf Distanz ist die Annahme nahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
3
0
4
Order By: Relevance
“…The hypotheses H3 and H4 can therefore be confirmed. Similarly, other studies have shown that during the COVID-19 pandemic in early 2020, the development of ICT skills among student teachers was indeed at least partially driven forward [62][63][64]. The extent to which students' increased use of digital media can be sustainably consolidated and, at best, transferred to their own lesson design at a later stage remains open at this point [65].…”
Section: Use Of Digital Media At the Universitymentioning
confidence: 95%
See 1 more Smart Citation
“…The hypotheses H3 and H4 can therefore be confirmed. Similarly, other studies have shown that during the COVID-19 pandemic in early 2020, the development of ICT skills among student teachers was indeed at least partially driven forward [62][63][64]. The extent to which students' increased use of digital media can be sustainably consolidated and, at best, transferred to their own lesson design at a later stage remains open at this point [65].…”
Section: Use Of Digital Media At the Universitymentioning
confidence: 95%
“…According to the Technology Acceptance Model (TAM), the use of a technology depends on the intention to use it, which in turn is determined by the subjectively perceived user-friendliness and the perceived benefits of a technology [60,61]. This is why an adaptive further training concept that is adapted to the previous experience of the teachers is still of importance as Schwabl and Vogelsang demand for preservice teachers [62].…”
Section: Use Of Digital Media In Schoolmentioning
confidence: 99%
“…Especially teacher training towards media literacy seems to be insufficient and does not meet the requirements of the KMK (Maxton-Küchenmeister & Meßinger-Koppelt, 2020). The Covid-19pandemic significantly accelerated the digitalisation of higher education institutions in Germany, as, within a few weeks, teaching had to be converted to online teaching (Schwabl & Vogelsang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A focus of the students on media-didactic competences becomes clear, which, however, are primarily understood in the sense of application-oriented techniques and indicate that the students' perspective on media-pedagogical aspects is only slightly pronounced. (Lorenz & Endberg, 2019;Schwabl & Vogelsang, 2021). Zugleich zeigen aktuelle Forschungen, dass die Erwartungen an bereits vorhandene Medienkompetenzen der Nachwuchslehrkräfte hoch sind (Schmidt, 2020).…”
Section: Introductionunclassified
“…In der ICILS-Studie von 2018 zeigte sich jedoch, dass nur etwa die Hälfte der befragten Lehrkräfte angab, im Rahmen der Ausbildung gelernt zu haben, digitale Medien angemessen in ihren Unterricht zu integrieren (Gerick & Eickelmann, 2020). In weiteren Untersuchungen wurde zudem deutlich, dass Lehramtsstudierende digitale Medien eher zur Kommunikation und seltener für Lernprozesse nutzen Schwabl & Vogelsang, 2021). Auch im Hinblick auf selbsteingeschätzte digitale Kompetenzen fanden sich Nachteile für Lehramtsstudierende (Senkbeil et al, 2020).…”
Section: Introductionunclassified